2013
DOI: 10.1089/ten.tec.2012.0166
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic Differentiation of Immortalized Human Mesenchymal Stem Cells on Zirconia Microwell Substrata

Abstract: Human mesenchymal stem cells (hMSCs) that can differentiate into chondrocytes are a potential autologous cell source for repair of damaged tissue. Current methods usually induce the formation of all three chondrocyte phenotypes, hyaline, fibrous, and elastic, without the ability to selectively induce only one of them. By controlling the size of hMSC cell clusters, it may be possible to direct differentiation more uniformly toward hyaline chondrocytes. We designed new cell culture platforms containing microwell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…5 ). In contrast, conventional pellet culture is reported to lead to heterogeneous matrix deposition [Mackay et al, 1998;Babur et al, 2013;Kitagawa et al, 2013], but it remains a widely accepted gold standard for studying redifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…5 ). In contrast, conventional pellet culture is reported to lead to heterogeneous matrix deposition [Mackay et al, 1998;Babur et al, 2013;Kitagawa et al, 2013], but it remains a widely accepted gold standard for studying redifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that nanostructure surface enhanced the proliferation and osteogenic differentiation of the MSCs on titanium [23][24][25][26] . However, few studies were reported about the hMSCs behavior on the TZP with different surfaces 27,28) . We assumed that the microand nano-topography may have suitable configurations for hMSCs behavior.…”
Section: Introductionmentioning
confidence: 99%
“…For microscale tissue engineering, the spheroid size and microenvironmental cues such as extracellular matrix (ECM) play an important role in directing stem cell behavior1213. The size of mesenchymal stem cell (MSC) spheroid has been shown to influence its differentiation potential, with smaller spheroid directing more homogeneous chondrogenic differentiation towards hyaline chondrocytes whereas larger pellet producing more heterogeneous tissue14. Further, external microenvironmental cues in the form of matrix scaffold are often applied to direct stem cell differentiation.…”
mentioning
confidence: 99%